Penerapan Data Mining dalam Mengelompokkan Kunjungan Wisatawan ke Objek Wisata Unggulan di Prov. DKI Jakarta dengan K-Means - Linda Maulida (UIN Sunan Kalijaga Yogyakarta, 2018)
Visits of foreign tourists to Indonesia can increase the country's foreign exchange and improve the economy of people in tourist areas. Jakarta is the capital of Indonesia which became one tourist destination for tourists. There are 8 leading tourist attraction in DKI Jakarta province according to BPS data of Prov. DKI Jakarta 1) Taman Impian Jaya Ancol, 2) Taman Mini Indonesia Indah, 3) Kebon Binatang Ragunan, 4) National Monument, 5) National Museum, 6) Satria Mandala Museum, 7) Jakarta History Museum And 8) Sunda Kelapa Harbor . The purpose of this study is to analyze the application of datamining in classifying the number of foreign tourists visiting the Prov. DKI Jakarta using k-means. The source of research data is from BPS Prov. DKI Jakarta. The research data used is the number of tourist visitors in 2007-2013 in accordance with BPS Prov. DKI Jakarta. The data are grouped into 3 clusters namely C1 = the number of high tourist visits, C2 = the number of tourists visiting medium and C3 = the number of tourist visits is low. The final centroid value used at C1 = 15.438.488, C2 = 4.464.577 and C3 = 342.332. So that the result of grouping C1 = Taman Impian Jaya Ancol, C2 = Taman Mini Indonesia Indah Dan Kebon Binatang Ragunan and C3 = National Monument, National Museum, Satria Mandala Museum, Jakarta History Museum and Sunda Kelapa Harbor. The result of C3 grouping becomes a record for the government of Prov. DKI. Jakarta.